On Minnesang in the database - Schlechter, Armin; Zimmermann, Karin; Miller, Matthias (German research, 2004)
The mediaeval German manuscripts at the Heidelberg University Library are cultural and historical records of great significance. Comprehensive cataloguing is making the collection newly accessible for research